2018
DOI: 10.1161/circgen.118.002157
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Branched-Chain Amino Acids and Incident Cardiovascular Disease in a Prospective Cohort of US Women

Abstract: Background Circulating branched-chain amino acids (BCAAs; isoleucine, leucine, valine) are strong predictors of type 2 diabetes (T2D), but their association with cardiovascular disease (CVD) is uncertain. We hypothesized that plasma BCAAs are positively associated with CVD risk, and evaluated whether this was dependent on an intermediate diagnosis of T2D. Methods Participants enrolled in the Women’s Health Study prospective cohort were eligible if free of CVD at baseline blood collection (N=27,041, mean base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
135
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 45 publications
10
135
0
Order By: Relevance
“…Our study has several limitations. First, the association of HF and BCAAs was based on a single measurement on banked samples in a repository for years, although many studies have also used samples with storage time ranging from 6 months to 22 years . The HKDR was established as a research‐driven quality improvement program using standard protocols for procedures, data collection, and sample processing/storage to minimize analytical errors.…”
Section: Strengths and Limitationssupporting
confidence: 56%
See 2 more Smart Citations
“…Our study has several limitations. First, the association of HF and BCAAs was based on a single measurement on banked samples in a repository for years, although many studies have also used samples with storage time ranging from 6 months to 22 years . The HKDR was established as a research‐driven quality improvement program using standard protocols for procedures, data collection, and sample processing/storage to minimize analytical errors.…”
Section: Strengths and Limitationssupporting
confidence: 56%
“…In a post hoc, nested case‐control analysis of the Prevención con Dieta Mediterránea (PREDIMED) trial involving 970 individuals at high cardiovascular risk (51% with T2D), those in the highest quartile of fasting plasma BCAAs at baseline had 70% excess risk of CVD than individuals in the lowest quartile . In the U.S. Women's Health Study of 27 041 female health professionals (2.6% with T2D), every SD increase in plasma BCAAs at baseline was independently associated with 13% excess risk of CVD during a 19‐year follow‐up period, an effect size comparable to every SD increase in LDL‐C . Likewise, carotid intima‐media thickness, a surrogate marker of ASCVD, was also positively associated with circulating levels of BCAAs in general populations of European and Chinese ancestry …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Elevations in several metabolites associated with high CD including BCAAs, PC, and PE may also suggest an increased risk of cardiovascular disease among athletes who belong to this group. Whereas BCAAs were previously correlated with increased risk of cardiovascular disease, 36 PC were shown to be associated with increased cardiovascular mortality independent of traditional risk factors. 37 PE (precursors of PC) have also been shown previously to be among the strongest predictive lipid species for risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 98%
“…Previously studied as the basis of an autosomal recessive metabolic disorder called maple syrup urine disease (MSUD) (Lu et al, 2009), the accumulation of BCAAs has been implicated in cardiac pathogenesis with metabolic reprogramming deemed vital in the progression of heart failure in mice and conserved in the metabolic signature of failing human hearts (Sun et al, 2016; Sun & Wang, 2016). A decrease in energy metabolism and increase in BCAA metabolism has further been associated with high‐glucose‐induced cardiomyocyte death (Zhang et al, 2018), and found to be a reliable predictor of susceptibility to type 2 diabetes, thereby circulating plasma BCAAs were also positively associated with incident cardiovascular disease (CVD) in U.S. Women (Tobias, Lawler, et al, 2018). These studies, among others, have collectively concluded that altered BCAA metabolism and consequently the accumulation of BCAA breakdown byproducts may herald insulin resistance and manifest as cardiometabolic disease.…”
Section: Discussionmentioning
confidence: 99%